Source model of the 16 September 2015 Illapel, Chile, Mw 8.4 earthquake based on teleseismic and tsunami data. Issue 2 (23rd January 2016) - Heidarzadeh, Mohammad; Murotani, Satoko; Satake, Kenji; Ishibe, Takeo; Gusman, Aditya Riadi
Abstract: We proposed a source model for the 16 September 2015 Illapel (Chile) tsunamigenic earthquake using teleseismic and tsunami data. The 2015 epicenter was at the northernmost of the aftershocks zone of the 2010 Mw 8.8 Maule earthquake. Teleseismic body wave inversions and tsunami simulations showed optimum rupture velocities of 1.5–2.0 km/s. The agreement between observed and synthetic waveforms was quantified using normalized root‐mean‐square (NRMS) misfit. The variations of NRMS misfits were larger for tsunami data compared to the teleseismic data, because tsunami waveforms are more sensitive to the spatial distribution of slip. The large‐slip area was 80 km (along strike) × 100 km (along dip) with an average slip of 5.0 m and depth of 12–33 km, located ~70 km to the northwest of the epicenter. We obtained a seismic moment of 4.42 × 10 21  Nm equivalent to Mw 8.4. Results may indicate a northward stress transfer from the 2010 Maule earthquake. Key Points: Large slip was in area 80 km × 100 km with average slip 5 m at depth 12–33 km Rupture velocity: 1.5–2 km/s from both teleseismic and tsunami data Rupture started near the northern end of 2010 Maule event propagating northward